Fernanda Seixas, a Woman’s Take on Architecture as Social Intervention - Sucena, Sara; Castro Ferreira, João (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
This paper sheds light upon architect Fernanda Seixas (1942-2017) as a trailblazing woman in her disciplinary field in Portugal. Her archives, a set of interviews, and bibliographical research allow us to pinpoint certain characteristics that make her stand out amongst her peers, and consider her as a woman succeeding in a ‘male profession’. Trained during an era of political dissent in which she actively participated against the dictatorship of Estado Novo in the 1960s, Seixas created her own practice right after the 1974 revolution and envisaged her work as a space of socio-political activism. In the 1980s her social consciousness broadened to include environmental concerns and she became a pioneering architect on the issues of energy efficiency and bioclimatic architecture. This technical approach combined with her social ethos stand out in her planning projects and built work.